Implementation of The Murottal Method in Memorizational-Qur'an at TPQ Al-Muhajirin - Tumangger, Adnan; Junaidi, Junaidi (LP. Ma'arif Janggan Magetan, 2024)
This article aims to analyze the implementation of the murottal method in memorizing the Qur'an at TPQ al-Muhajirin. Indonesia, whose majority population is Muslim, is able to produce a young generation who memorize the Koran. Unfortunately, the intensity of memorizing the Koran in Indonesia is still less than that of Saudi Arabia when viewed from a ratio perspective. Memorizing the Qur'an has many lessons and advantages, unfortunately people still cannot identify these benefits. The urgency of this research is to produce a relevant method for memorizing the Al-Qur'an so that the intensity of memorizing the Al-Qur'an in Indonesia can increase. This article uses a qualitative method with a descriptive-narrative approach. The data collection techniques used in this article are interviews, observation and documentation. The primary data sources in this research are the founders, teachers and students of TPQ al-Muhajirin. Meanwhile, the secondary data used are books, articles and reports relating to the discussion. The collected data will be analyzed using content analysis techniques. The research results showed that TPQ al-Muhajirin used the murottal method in memorizing the Al-Qur'an. This method is implemented in three periods: 1) Introduction, 2) Training and 3) Post-training. Then, the advantages of memorizing using the murottal method are 1) Strengthening memorization through hearing, 2) Setting tempo and rhythm, 3) Concentration, 4) Audio-visual associations, 5) Appreciation and sincerity and 6) Flexibility and accessibility. Cumulatively, the murottal method for memorizing the Al-Qur'an is considered effective because it is able to generate high interest in memorizing and create students who excel in competitions.